Identification of measurements of students' physical fitness levels in basketball extracurriculars - Ilmul Ma’arif (International Journal of Basketball Studies, 2023)
This study aims to determine the level of physical fitness of students who participate in basketball extracurriculars, The method used in this study is a survey method. The sampling technique used total sampling, so that the entire population of 25 students was made the subject of this study. The instrument in this study is a physical fitness test to measure fitness levels. The results of data analysis in this study showed that students who participated in extracurricular basketball on each item of the physical fitness test showed a percentage value for the BMI test 72% Normal category, sit up 60 seconds 40%, sit and reach 44%, pull up modification test 40%, run 20 m 52%, So that the results of the analysis entered the moderate category, So it can be concluded that the physical fitness level of basketball extracurricular students is in the moderate category.